Ideal citizens: the birthing of state truths and fictions in Quintana Roo. Issue 3 (1st September 2016) - Williams, Sarah A.
ABSTRACT: Reducing the maternal mortality rate (MMR) is an important part of Mexico's commitment to the Millennium Development Goals, and the country has made great strides towards achieving this goal. However, researchers have questioned to what extent the focus on improved MMR and other indices of maternal health has contributed to an emphasis on improved statistics rather than quality care, and the effect this has had on the quality of reporting. While public health officials and hospital administrators alike agree that improved obstetric reporting is necessary, there is little discussion regarding the accuracy of the data that are submitted and the institutional pressures that may contribute to the production of inaccurate data. Using ethnographic research collected in Tulum, Quintana Roo, this paper explores how biomedical childbirth functions as a source of legitimization for the state while simultaneously providing the means for the presentation of an ideal subjecthood, one that situates birthing women and healthcare personnel as properly attenuated to the norms and needs of the modern Mexican state. By highlighting the point of disjuncture between women's experiences and the formal 'reality' created through hospital texts, this paper explores the place of biomedical birth as a producer of and legitimization for Mexican public health policy.